PENGARUH KEMAMPUAN PRODUKSI, LUAS LAHAN DAN BIAYA PRODUKSI TERHADAP JUMLAH PRODUKSI SERTA PENDAPATAN PETANI PISANG - Wiguna, I Putu Agus Ari; Purbadharmaja, Ida Bagus Putu (Buletin Studi Ekonomi; VOL.24.NO.1.FEBRUARI 2019DO - 10.24843/BSE.2019.v24.i01.p07, 2019)
Abstract: Effect of Production Capability, Land Area and Production Costs on Production Amounts and Banana Farmer Income. This research was conducted in Selemadeg Barat District, Tabanan Regency with respondents from banana farmers covering the area of each village in Selemadeg Barat District, Tabanan Regency. The sampling technique used is Simple Random Sampling. Sample in this study amounted to 92 respondents. This study uses path path analysis techniques to analyze the direct influence between variables one with other variables and the sobel test analyzes indirect effects through intervening variables. Based on the results of the study concluded that the production capacity, land area, and production costs have a positive and significant effect on the amount of banana production in the Selemadeg Barat District. Production capability has a positive and insignificant effect on the income of banana farmers in Selemadeg Barat District. Production costs have a negative and insignificant effect on the income of banana farmers in Selemadeg Barat District. Production capability, land area, and production costs have an indirect influence on the income of banana farmers through the amount of production in the District of West Selemadeg.